Stress management (International Journal of Scientific Research and Management (IJSRM), 2016)
Stress is conceived as pressure from the environment, then as strain within the person. The generally accepted definition today is one of interaction between the situation and the individual. It is the psychological and physical state that results when the resources of the individual are not sufficient to cope with the demands and pressures of the situation. Thus, stress is more likely in some situations than others and in some individuals than others. Stress can undermine the achievement of goals, both for individuals and for organisations Dealing with stress-related claims also consumes vast amounts of management time. So, there are clearly strong economic and financial reasons for organisations to manage and reduce stress at work, aside from the obvious humanitarian and ethical considerations. Stress can undermine the achievement of goals, both for individuals and for organisations